An Efficient Zero-Stable Numerical Method for Fourth-Order Differential Equations - S. J. Kayode (International Journal of Mathematics and Mathematical Sciences)
The purpose of this paper is to produce an efficient zero-stable numerical method with the same order of accuracy as that of the main starting values (predictors) for direct solution of fourth-order differential equations without reducing it to a system of first-order equations. The method of collocation of the differential system arising from the approximate solution to the problem is adopted using the power series as a basis function. The method is consistent, symmetric, and of optimal order 𝑝=6. The main predictor for the method is also consistent, symmetric, zero-stable, and of optimal order 𝑝=6.